Relationships between volunteerism, job performance and life satisfication among healthcare volunteers in Malaysia - Veerasamy, Chanthiran (2012)
This exploratory research investigated the relationship between Volunteerism (ISBV),Job Performance (JP) and Life Satisfaction (LS) among Volunteers in Malaysia. Volunteering is said to be a significant activity which runs throughout the world and in particular it is an essential part of the Malaysian society. Therefore this activity needed to be studied in order to help the development of community and the organisation of volunteerism. Up to now the literature shows that very little academic research had been carried out on volunteerism in Malaysia especially research investigating the relationship of volunteerism towards job performance and life satisfaction among volunteers. A mailed survey was carried out with a sample of 366 volunteers with a 36% response rate of correctly completed questionnaires. The data collected from the volunteers included Personality, Motives, Human and Cultural Capital (Subjective Well Being, Religiosity and Spirituality), Employer Encouragement, Self Esteem, Job Performance and Life Satisfactions, and all the variables were self rated by the respondents. Meanwhile the data analysis was carried out using descriptive and inferential statistics. The descriptive analysis showed the profile of respondents and perceptions on personality, motives, Human and Cultural Capital (Subjective Well Being, Religiosity and Spirituality), Volunteerism, Job Performance and Life Satisfaction for volunteerism. The inferential statistics was used to compute difference of mean, relationship and the moderation effect and the Hierarchical Regression was used to predict the volunteerism (I-SBV). The study investigated the moderating effect of the Employer’s Encouragement and Self Esteem between Volunteerism (I-SBV), Job Performance and Life Satisfaction. The findings of this study provided a better understanding of the predictors of Volunteerism (ISBV) and its contribution towards high, sustained Job Performance and Life Satisfaction of volunteers. Besides that, the employer’s encouragement and self esteem had been identified as a moderator between Volunteerism, Job Performance and Life Satisfaction. The exploratory study provides a data-base to develop new strategies, further research and review of the social policy.